Opportunities to Increase Halal SMEs Income: Evidence from Muslim Minority Area - Awirya, Agni Alam; Nainggolan, Cesilia Natasya; Susilo, Andi Joko; Puspita, Novi Dwi (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
The growth of halal products and businesses in areas with minority Muslim populations, such as Papua, Indonesia, presents both distinct challenges and opportunities. This study examines the development of Halal-certified Small and Medium Enterprises (SMEs) in Papua, a region with a minority Muslim population. Using primary data from 33 Halal-certified SMEs in Jayapura, the research investigates the factors that affect income growth following Halal certification. Data were collected using non-probabilistic sampling and analyzed through descriptive statistics and logistic regression. The results show that entrepreneurial age and business tenure positively impact income growth, emphasizing the value of experience. However, market orientation (targeting markets outside Jayapura) has a negative effect, likely due to logistical challenges. Surprisingly, entrepreneurial education does not significantly influence income generation, suggesting that local knowledge and experience play a larger role. The study recommends that Halal SMEs focus on enhancing workforce management, confidence, and marketing strategies to improve competitiveness and market expansion. These findings offer valuable insights for fostering the growth of Halal-certified SMEs in minority regions and supporting sustainable economic development in Papua.